INTRODUCTION TO THE RELATIONSHIP BETWEEN MODERNITY AND SOCIOLOGY IN SPECIFIC TO EMILE DURKHEIM AND MAX WEBER’S STUDIES - Alkin, Ruhi Can (European Scientific Journal, ESJ, 2014)
This paper proposes to examine the strong relationship among the emergence of modernity and foundation of sociology by investigating Emile Durkheim and Max Weber’s studies. Some of the arguments developed by these thinkers towards the process of social change will be analyzed. By focusing on Durkheim and Weber’s studies when dealing with the aforementioned relationship, it is proposed to illustrate two main methodological and theoretical considerations in sociology tradition. It will be claimed that Weber’s position towards social change represents the interpretative tradition in sociology whilst Durkheim was a defender of positivist methodology. Besides describing thinker’s scientific studies and their connection with modernity, Weber and Durkheim’s optimistic and pessimistic attitude towards social change will be questioned in conclusion part. This attempt may seem to be dealing with emotional reflections, which is generally explored by psychology. However, it will be seen that Durkheim and Weber’s long-term theoretical studies and methodological considerations in sociology characterize their attitude in the face of social change in 19th century. This assertion will be justified and detailed in the relevant section.